Gambaran Masa Pemulihan Sistem Kardiovaskular Berdasarkan Indeks Masa Tubuh pada Mahasiswa Fakultas Kedokteran XYZ - Febriyanti Zulyani; Fadya Millenia; Srimukti Suhartini; Sri Rahayu Ningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
Physical activity includes all body movements performed in working, playing, or traveling, while physical inactivity is characterized by minimal movement and low energy expenditure. Body Mass Index (BMI) and recovery heart rate are important indicators in assessing fitness status and health risks. This study aims to determine the difference in cardiovascular system recovery time after physical activity based on BMI category in students of the Faculty of Medicine, Gunadarma University. Students in this study are classified as late adolescents to early adults with typical lifestyles, such as lack of sleep, irregular eating patterns, academic stress, and low physical activity, which can impact the cardiovascular system. This study applied a cross-sectional design with purposive sampling technique among students who met the inclusion criteria. The research procedure was carried out in two stages, namely measuring blood pressure, pulse rate, O₂ saturation, and BMI before and after a six-minute walking test, then continued with measuring the pulse recovery time after a ±20-minute rest. Data were analyzed using paired T-test and One Way ANOVA according to data distribution. The majority of respondents were women (92.5%) from the class of 2019 (77.4%), with an average age of 20.79 years. The results showed a significant increase in systolic blood pressure and pulse rate after the physical test (p=0.001), while diastolic blood pressure showed no significant change (p=0.622). No significant difference was found in recovery time based on BMI categories (p=0.516). Therefore, it can be concluded that physical activity significantly influences several physiological parameters, particularly systolic blood pressure and pulse rate. However, BMI status was not shown to affect the speed of cardiovascular recovery after physical activity.